Gene Therapy Approaches - Ahmed Jumaa Ahmed; Hogir Saadi (Qubahan Academic Journal)
Gene therapy can be described broadly as the transfer of genetic material to control a disease or at least to enhance a patient's clinical status. The transformation of viruses into genetic shuttles is one of the core principles of gene therapy, which will introduce the gene of interest into the target tissue and cells. To do this, safe strategies have been invented, using many viral and non-viral vector delivery. Two major methods have emerged: modification in vivo and modification ex vivo. For gene therapeutic approaches which are focused on lifelong expression of the therapeutic gene, retrovirus, adenovirus, adeno-associated viruses are acceptable. Non-viral vectors are much less successful than viral vectors, but because of their low immune responses and their broad therapeutic DNA ability, they have advantages. The addition of viral functions such as receptor-mediated uptake and nuclear translocation of DNA may eventually lead to the development of an artificial virus in order to improve the role of non-viral vectors. For human use in genetic conditions, cancers and acquired illnesses, gene transfer techniques have been allowed. The ideal delivery vehicle has not been identified, although the accessible vector systems are capable of transporting genes in vivo into cells. Therefore, only with great caution can the present viral vectors be used in human beings and further progress in the production of vectors is required. Current progresses in our understanding of gene therapy approaches and their delivery technology, as well as the victors used to deliver therapeutic genes, are the primary goals of this review. For that reason, a literature search on PubMed and Google Scholar was carried out using different keywords.